Relationship between agility and jump ability in amateur beach volleyball male players - Busca, B.; Alique, D.; Salas, C.; Hileno, R.; Pena, J.; Morales, J.; Bantula, J. (International Journal of Performance Analysis in Sport, 2015)
Agility and quickness is required by the beach volleyball players, such as sudden falls, short sprints and jumps. The surface where the beach volleyball is played constitutes a different paradigm to study these actions. This paper analyses the relationship between the agility test and the ability to jump on the sand among beach volleyball players. The study also shows the relationship between the ability to jump on rigid and sand surface. Significant correlations were found between specific agility test and both jumps test on the sand and on the rigid surface (r=-0.62 and r=-0.75, respectively). Significant differences were also found in sand tests between the national- and regional-level players. In conclusion, there was a solid relationship between jumping ability and agility of beach volleyball players. Moreover, the results of the present study reflect a surface adaptation in jumping and agility actions of more experienced players.